FOREIGN EXPERIENCE IN IMPROVING THE ORGANIZATIONAL AND LEGAL FOUNDATIONS OF WATER SUPPLY MANAGEMENT - Mirzokirov, Mirabbos (Journal of Research and Development, 2026)
This article analyzes the improvement of the organizational and legal foundations of water management in Uzbekistan based on the experience of foreign countries. The objective of the study is to identify effective institutional and legal mechanisms in the field of water resource management and to assess the possibilities for their adaptation to national conditions. The research employs comparative legal analysis, a systems approach, case study, and institutional-functional analysis. Various models of water resource management are examined through the experiences of Israel, France, Russia, Belarus, and Armenia. The findings demonstrate that the implementation of the basin-based management principle, the integration of state regulation and market mechanisms, the application of economic instruments, and the clear distribution of institutional responsibilities are of critical importance for effective water resource governance. In conclusion, the study substantiates that the introduction of an integrated approach to water management and the targeted adaptation of foreign experience represent effective directions for improving the water management system in Uzbekistan.